Cytosolic, autocrine alpha-1 proteinase inhibitor (A1PI) inhibits caspase-1 and blocks IL-1β dependent cytokine release in monocytes. - Yonggang Wang; Yong He; Bindu Abraham; Farshid N Rouhani; Mark L Brantly; Dorothy E Scott; Jennifer L Reed (PLoS ONE, 2012)
RATIONALE: Activation state-dependent secretion of alpha-1 proteinase inhibitor (A1PI) by monocytes and macrophages was first reported in 1985. Since then, monocytes and tissue macrophages have emerged as key sentinels of infection and tissue damage via activation of self-assembling pattern recognition receptors (inflammasomes), which trigger inflammation and cell death in a caspase-1 dependent process. These studies examine the relationship between A1PI expression in primary monocytes and monocytic cell lines, and inflammatory cytokine expression in response to inflammasome directed stimuli. METHODS: IL-1 β expression was examined in lung macrophages expressing wild type A1PI (A1PI-M) or disease-associated Z isoform A1PI (A1PI-Z). Inflammatory cytokine release was evaluated in THP-1 monocytic cells or THP-1 cells lacking the inflammasome adaptor ASC, transfected with expression vectors encoding A1PI-M or A1PI-Z. A1PI-M was localized within monocytes by immunoprecipitation in hypotonic cell fractions. Cell-free titration of A1PI-M was performed against recombinant active caspase-1 in vitro. RESULTS: IL-1 β expression was elevated in lung macrophages expressing A1PI-Z. Overexpression of A1PI-M in THP-1 monocytes reduced secretion of IL-1β and TNF-α. In contrast, overexpression of A1PI-Z enhanced IL-1β and TNF- α secretion in an ASC dependent manner. A1PI-Z-enhanced cytokine release was inhibited by a small molecule caspase-1 inhibitor but not by high levels of exogenous wtA1PI. Cytosolic localization of A1PI-M in monocytes was not diminished with microtubule-inhibiting agents. A1PI-M co-localized with caspase-1 in gel-filtered cytoplasmic THP-1 preparations, and was co-immunoprecipitated with caspase 1 from nigericin-stimulated THP-1 cell lysate. Plasma-derived A1PI inhibited recombinant caspase-1 mediated conversion of a peptide substrate in a dose dependent manner. CONCLUSIONS: Our results suggest that monocyte/macrophage-expressed A1PI-M antagonizes IL-1β secretion possibly via caspase-1 inhibition, a function which disease-associated A1PI-Z may lack. Therapeutic approaches which limit inflammasome responses in patients with A1PI deficiency, in combination with A1PI augmentation, may provide additional respiratory tissue-sparing benefits.